2019
DOI: 10.1021/acs.energyfuels.9b00821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Suppressing Asphaltene Aggregation and Flocculation by Dodecylbenzenesulfonic Acid Probed by Molecular Dynamics Simulations

Abstract: The behaviors of an asphaltene model compound, N-(1-undecyldodecyl)-N′-(5-carboxylicpentyl)-perylene-3,4,9,10-tetracarboxylbisimide (C5PeC11), in the absence and presence of an asphaltene inhibitor, dodecylbenzenesulfonic acid (DBSA), in n-heptane and toluene solutions were studied using molecular dynamics simulation. The presence of DBSA was found to reduce both the rate and degree of C5PeC11 aggregation while increasing the solvation of C5PeC11 molecules in the solvents studied. A higher concentration of DBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…S.4, probably a sign of a preference of either one or the other to interact with this region of the simulation box). When demulsifiers are also present, such interactions are also lowered, probably due to the fact that demulsifiers interacting with porphyrins and/or asphaltenes reduce the interaction among these species and water, as it was recently indicated by Jiang et al (2019).…”
Section: With Demulsifiermentioning
confidence: 82%
“…S.4, probably a sign of a preference of either one or the other to interact with this region of the simulation box). When demulsifiers are also present, such interactions are also lowered, probably due to the fact that demulsifiers interacting with porphyrins and/or asphaltenes reduce the interaction among these species and water, as it was recently indicated by Jiang et al (2019).…”
Section: With Demulsifiermentioning
confidence: 82%
“…The average number of hydrogen bonds between the molecular model, as well as the molecular model and water, was calculated to determine the influence of DDA and NaOL molecules on the stability of aggregate with different molar ratios ( Table 2 ). In our simulation, r DA (distance between donor-acceptor) ≤ 0.35 nm and θ ADH (angle of acceptor-donor-hydrogen) ≤ 30° were chosen to use as the standard for calculating a hydrogen bond [ 36 , 43 ]. We observed that hydrogen bond did not form between identical molecules in all systems, such as DDA-DDA and NaOL-NaOL.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent MD simulations and analysis of the behavior of surfactants in aqueous solution were completed by virtue of Gromacs2018 and its built-in analytical tools. VMD 1.9.3 was used to visualize the evolution of molecular structures varying with time [ 29 , 35 , 36 ]. The structure files of NaOL and DDA were imported into ATB (Automated Topology Builder) to establish the initial topology files after optimizing [ 36 , 37 , 38 ], which was a significant foundation to implement molecular dynamics successfully.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-molecule asphaltene dispersants include acidic amphiphilic molecules, amides and imides and ionic liquids [6,7]. For example, dodecyl benzene sulfonic acid (DBSA) and dimethyl amide (DA) can form hydrogen bonds with asphaltene molecules, generating acid-base force to prevent the aggregation of asphaltenes and improve the fluidity of crude oil [8,9]. However, most small-molecule asphaltene dispersants have problems such as a high cost of preparation and poor compatibility with different crude oils.…”
Section: Introductionmentioning
confidence: 99%